2008
DOI: 10.3928/01477447-20110505-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Olecranon Resection on Joint Stability and Strain of the Medial Ulnar Collateral Ligament

Abstract: This study aimed to assess the effect of posteromedial olecranon resection on the stability of the elbow joint, forearm kinematics, and strain in the anterior bundle of the medial ulnar collateral ligament. Seven elbows were tested after resecting all soft tissues except the capsuloligamentous structures. Varus-valgus angulation, forearm rotation, and the length of the anterior bundle of the medial ulnar collateral ligament were measured at 3 posteromedial olecranon resection stages of 0, 4, and 8 mm, and at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It is also possible that the adaptive change theory may again be at play, with athletes feeling less satisfied because of removal of adaptive posterior compartment osteophytes. 12 , 13 , 18 , 19 , 20 Ultimately, postoperative PROs were largely the same between the two groups. Despite having identical protocols, two of the PI group athletes mentioned the rehabilitation process as the reason why they would not re-elect for the procedure; thus, patient dissatisfaction may have been secondary to difficulties with rehabilitation rather than the procedure itself.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is also possible that the adaptive change theory may again be at play, with athletes feeling less satisfied because of removal of adaptive posterior compartment osteophytes. 12 , 13 , 18 , 19 , 20 Ultimately, postoperative PROs were largely the same between the two groups. Despite having identical protocols, two of the PI group athletes mentioned the rehabilitation process as the reason why they would not re-elect for the procedure; thus, patient dissatisfaction may have been secondary to difficulties with rehabilitation rather than the procedure itself.…”
Section: Discussionmentioning
confidence: 81%
“…Some authors argue that posterior compartment osteophytes, secondary to olecranon fossa shearing, may be adaptive changes to the thrower’s elbow, and that arthroscopic resection may destabilize the elbow. 12 , 13 , 18 , 19 , 20 Kamineni et al., indeed, demonstrated that excessive resection of posteromedial osteophytes leads to increased translation of the olecranon during elbow motion and a resultant increase in strain on the anterior bundle of the UCL. 12 , 13 While there was no difference in mean KJOC or Andrews-Timmerman scores in our analysis, there was a higher mean KJOC-Control score in the no impingement group (9.11 ± 1.32 vs 7.65 ± 2.40; P = .04), which may be explained by this destabilization theory following resection of posteromedial osteophytes.…”
Section: Discussionmentioning
confidence: 99%
“…10). It is crucial to only resect the osteophyte, since with excessive bone resection, there is potential for developing elbow instability and subsequent ulnar collateral ligament (UCL) tear [10,11].…”
Section: Excision Of Olecranon Osteophytesmentioning
confidence: 99%